math
posted by barry .
simplify this expression (3xy)^2(2x^2z)^3

(3xy)^2 = 3^2 x^2 y^2 = 9 x^2 y^2
(2x^2z)^3 = 2^3 (x^2)^3 z^3 = 8 x^6 z^3
multiplying all that, we get
72 x^8 y^2 z^3
Respond to this Question
Similar Questions

AlgebraPlease check my answers
Posted by Jessie on Monday, October 18, 2010 at 3:48pm. I think I figured it outplease check I'm really stuck on these problems Simplify 6xy(3xy)^2? 
AlgebraPlease check my answers
Posted by Jessie on Monday, October 18, 2010 at 3:48pm. I think I figured it outplease check I'm really stuck on these problems Simplify 6xy(3xy)^2? 
Math
How do you factor: 9x^2y^3  3x^3y^2  15xy i got: 3xy(3xy^2  x^2y  5) But how do you factor it further to simplify it? 
algebra
add if possible simplify the expression (8x^3y^2+5x^2y^2+6xy^2)+(4x^3y^23xy^2) 
Algebra
Simplify the rational expression (x^2+xy2y^2)/(x^2+3xy+2y^2) 
Algebra 2
Simplify the rational expression (x^2+xy2y^2)/(x^2+3xy+2y^2) 
Math!
1) What is the value of 19 + 5a^4 + 3b^2 when a = 2 and b = 4? 
Simultaneous equation
X+y+z=1......(1) x^2+y^2+z^2=35........(2) x^3+y^3+z^3=97.........(3) solution but from 3 (x^3+y^3)=(x+y)^33xy(x+y)......(4) puting 4 into 3 bck (x+y)^33xy(x+y)+z^3=97.......(5) now from 1 x+y=1z......(6) putin 6 into 7 we have … 
urgent math
1. Simplify the expression 7^9/7^3 a.7^3*** b.7^6 c.7^12 d.1^6 2. Simplify the expression z^8/z^12 a.z^20 b.z^4 c.1/z^4 d.1/z^4 3. Simplify the expression (3^4)/(3^4 a.(3)^1 b.0 c.1 d.(3)^8 4.Which expressions can be rewritten … 
polynomials
I have to simplify (x^5y^4)^4(3x^2y)^2(1/3xy) I did (x^20y^16)(9x^4y^2)(1/3xy) (9x^24y^18)(1/3xy) 3x^25y^19 Is this correct?